Evaluation of Cortisol and Heat Shock Proteins in Rabbits Under Cadmium-Induced Stress and Chelation Therapy: Evaluasi Kortisol dan Protein Kejut Panas pada Kelinci yang Mengalami Stres yang Diinduksi Kadmium dan Terapi Khelasi - Sadiq, Dina H.; Hussein, Diyar Mohammad (Indonesian Journal on Health Science and Medicine, 2025)
Background: Cadmium (Cd) exposure poses a significant environmental and occupational health concern, as it induces oxidative stress and disrupts cellular homeostasis. This study investigated the cadmium-induced stress response by examining its effects on cortisol and heat shock protein expression in rabbits, as well as the potential use of chelation therapy. Methods: Thirty-six New Zealand White rabbits were randomly divided into four groups (n=9) - control, cadmium exposure group (5 mg/kg CdCl₂ for 28 days), chelation therapy group (cadmium exposure and DMSA treatment at 50 mg/kg for 14 days), and DMSA group only. Serum cortisol levels were measured using an enzyme-linked immunosorbent assay (ELISA) method. The expression levels of heat shock protein 70 (HSP70) and HSP90 were evaluated using Western blot on liver and kidney tissue. Results: Cadmium exposure increased serum cortisol (48.3 ± 6.2 ng/mL vs. 22.1 ± 3.4 ng/mL in controls, p<0.001). Cadmium exposure also increased HSP70 and HSP90 in liver (3-fold and 2.8-fold, respectively) and kidney (2.9-fold and 2.5-fold, respectively) tissues. Furthermore, chelation therapy with DMSA reduced serum cortisol to 31.7 ± 4.8 ng/mL (p < 0.01) and somewhat reversed heat shock protein levels. Conclusion: Cadmium exposure is a significant source of physiological stress in rabbits, as evidenced by increased serum cortisol levels and post-exposure expression of heat shock protein (HSP). DMSA chelation therapy has therapeutic effects for reducing cadmium-induced stress response, and shows potential value as a treatment plan for cadmium poisoning patients.Highlight : Cadmium exposure significantly elevates cortisol and heat shock proteins, indicating systemic and cellular stress in rabbits. DMSA chelation therapy partially reduces these stress markers, showing potential as a treatment for cadmium poisoning. The correlation between cortisol and HSP expression suggests integrated biomarkers can assess cadmium-induced stress effectively. Keywords : Cadmium Toxicity, Cortisol, Heat Shock Proteins, Chelation Therapy, DMSA